Lung Transplant Recipient with Pulmonary Alveolar Proteinosis. (24th April 2016) - Tokman, Sofya; Hahn, M. Frances; Abdelrazek, Hesham; Panchabhai, Tanmay S.; Patel, Vipul J.; Walia, Rajat; Omar, Ashraf
Abstract : Pulmonary alveolar proteinosis (PAP) is a progressive lung disease characterized by accumulated surfactant-like lipoproteinaceous material in the alveoli and distal bronchioles. This accumulation is the result of impaired clearance by alveolar macrophages. PAP has been described in 11 solid organ transplant recipients, 9 of whom were treated with mammalian target of rapamycin inhibitors. We report a case of a lung transplant recipient treated with prednisone, mycophenolate mofetil (MMF), and tacrolimus who ultimately developed PAP, which worsened when MMF was replaced with everolimus.